Feeding Practices in Very Preterm and Very Low Birth Weight Infants in an Area Where a Network of Human Milk Banks Is in Place - Berti, Elettra; Puglia, Monia; Perugi, Silvia; Gagliardi, Luigi; Bosi, Cristiana; Ingargiola, Anna; Magi, Letizia; Martelli, Elena; Pratesi, Simone; Sigali, Emilio; Tomasini, Barbara; Rusconi, Franca (Frontiers in Pediatrics, 2018)
Background. Great variability in enteral feeding practices for very preterm (<32 weeks gestational age-GA) and very low birth weight infants (VLBW; ≤1,500g) have been reported. We aimed to describe data on enteral feeding in Tuscany (Italy), where a network of 6 donor milk banks is in place. Methods. A 4-year (2012-2015) observational study was performed analyzing the database “TIN Toscane online” on very preterm and VLBW infants. The database covers all 25 hospitals with a neonatal unit. Results. Data concerning the beginning of enteral nutrition were available for 1,302 newborns with a mean (standard deviation) GA of 29.3 (2.9) weeks, while information at the time of full enteral nutrition was available for 1,235 and at discharge for 1,140. Most infants (74.1%) started enteral feeding during the first 24 hours of life. Overall, 80.1% of newborns were fed exclusive human milk, donor milk having the larger prevalence of use (66.8%). Few infants (13.3%) started with exclusive mother’s milk. Full enteral feeding was achieved using exclusive human milk in most cases (80%). Full enteral feeding was reached earlier in newborns who were fed human milk than in those fed formula, regardless of GA. Sixty-four percent of infants were still fed with any human milk at discharge. When data at the achievement of full enteral nutrition and at discharge were analyzed stratified by the type of milk used to start enteral feeding, newborns initially fed donor milk presented the highest prevalence (91.3%) of exclusive human milk at full enteral feeding, an important period to prevent necrotizing enterocolitis, while no differences were observed at discharge. Conclusions. Donor milk was widely used for newborns during the first hours of life, when mother’s milk availability may be quite challenging. Starting enteral nutrition with donor milk was associated with early start of enteral feeding and early achievement of full enteral nutrition without affecting mother lactation. The overall prevalence of human milk at discharge (when donor milk is not available anymore) was high (64%), irrespective of the type of milk used to start nutrition.